PENERAPAN FETAL MOVEMENT COUNT EDECATION TERHADAP TINGKAT PENGETAHUAN IBU HAMIL PRIMIGRAVIDA TRIMESTER II - Handayani, Jesika; Anggi, Geuis; Darmayanti (Jurnal Kesehatan An-Nuur, 2024)
Low levels of knowledge and awareness of the importance of monitoring fetal well-being can have a negative impact, even triggering increased hemorrhage and intrauterine fetal death. (IUFD). The purpose of this case study is to raise the knowledge and awareness of pregnant mothers about the importance of monitoring the well-being of the fetus independently. This case study was shown to pregnant primegravid mothers at the age of 14-28 weeks of pregnancy to perform fetal movement calculations. The intervention used in this case study was an education and demonstration counting fetal movement for 12 hours. The results of the case study showed an increase in the mother's knowledge of fetal motion from 62.5 to 83.3 on the last day of the intervention. It could indicate that there was an increase in knowledge. Application of the fetal Movement count education to pregnant mothers gives awareness of the importance of fetal monitoring.